Enhanced thermoelectric performances in graphene nanoribbons via BN dimers doping: Theoretical study - Fouad N. Ajeel; Ali Ben Ahmed (Chemical Physics Impact, 2024)
Improving the thermoelectric performance of designed graphene nanoribbons is a key stage in the production of thermoelectric nanodevices with many applications. The chemical doping allows armchair graphene nanoribbons (AGNRs) to exhibit controllable thermoelectric characteristics. Here, we use density functional theory-based tight-binding (DFTB) coupled with the non-equilibrium Green's function (NEGF) to study the electronic and thermoelectric properties of AGNR with boron nitride (BN) dimers at room temperature. Changing the concentrations (from 4.17 % (BN)1-structure to 12.5 % (BN)3-structure) and geometrical pattern (ortho, meta, and para form) of BN dimers in the graphene nanoribbons may have a significant effect on the thermoelectric (TE) properties. Our results show that the TE properties of AGNR depend not only on the amount of BN dimers but also on the arrangement of the BN dimers in the AGNR. The thermoelectric figure of merit (ZT) of nanoribbons at room temperature has improved from less than 0.7 to more than 2. These results could be used as an indicator to design nanodevices that have good TE applications.